Diagnóstico bacteriológico de la tuberculosis en Argentina: resultados de una encuesta nacional - Imaz, María Susana (2007)
In order to assess laboratory resources, practices, and biosafety measures during mycobacterial testing and determine the usefulness and scope of mycobacterial techniques, a cross-sectional survey of public laboratories was conducted in Argentina using a structured questionnaire. Sputum smear analysis showed that both smear and culture testing centers are being provided at or above the WHO recommended density for such facilities. The microscopy quality assessment program covered most high-demand laboratories. Mean number of sputum smears per patient was low (1.6). The use of inadequate personal respiratory protection was identified in 25% of culture laboratories. Jurisdictions that cultured a higher proportion of their smear-tested sputa identified a higher proportion of smear-negative cases. The percentage of smear negatives among all bacteriologically confirmed pulmonary cases was 18.9%, while most extrapulmonary cases were confirmed by culture (71.3%). In conclusion, increasing the number of sputa studied by microscopy and culture (while expanding the coverage of the quality assessment program) is a priority; adequate respiratory protection and regular medical evaluation of laboratory staff is still needed in some laboratories.